IDENTIFIKASI LAPISAN AKUIFER AIR TANAH BAWAH PERMUKAAN METHOD GEOLISTRIK TEKNIK VES (Vertical Electrical Sounding) PADA LOKASI RENCANA PEMBORAN AIR TANAH DALAM LOKASI GUNUNG BALE KABABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Syamsul Syukur; Abdul Syakur (Agroland: Jurnal Ilmu-ilmu Pertanian, 2020)
The study aims to identify the existence of aquifer of subsurface groundwater. The study took place in September 2019 by identifying the subsurface soil aquifer located at the official residence of Chairman of Parliament in Donggala regency, Central Sulawesi province. The method used in the study was VES (Vertical Electrical Sounding) which is one of the methods in geoelectricity. The results showed that the best aquifer of groundwater located at >20 m depth below ground level (bgl) with layer thickness is around 30 m and at  >70 m depth bgl with layer thickness is > 30 m (based on measurement trajectory located in the Village of G. BALE). The aquifer lies on the third layer which is intermediate to high aquifer with lithology in the form of sandstone and medium to rough-grained sand. Keywords: Aquifer, Geoelectricity Method, and Groundwater.